Risk and Capitalist Power: Conceptual Tools for Studying the Political Economy of Hollywood - James McMahon (The Political Economy of Communication, 2015)
In this article, the structure of Hollywood film distribution will be analyzed through the lens of risk. In both its technical and conceptual senses, risk is relevant to the study of Hollywood's dominant firms. In the interest of lowering risk, the business interests of Hollywood look to predetermine how new films will function in an already instituted order of cinema, which includes the creativity of filmmakers and the habits of moviegoers. This presentation of risk will explain why, for the political economy of Hollywood, the social world of cinema is an instrumental order. While risk is specifically about the size and pattern of future earnings, it is also an indirect prediction about the stability of the social conditions that would help translate potential earnings into an actual stream. The social world of cinema has a bearing on the Hollywood film business's degree of confidence, which refers to the ability of capitalists to make predictions about future earnings.
Keywords: 330; capitalization; cinema; Hollywood; risk